O homog??neo no heterog??neo: o Sinaes e as din??micas da gest??o na educa????o superior privada - Mendes, Ana Luiza Fernandes (2016)
This research investigated the management dynamics in a Higher Education Institution (HEI) Private of Bahia western on the demands of the policy of the National Higher Education Evaluation System (Sinaes). This scenery is marked by de regulation, and by the rankings in the higher education. This is a qualitative case study, without giving up the use of quantitative data. The adopted approach is supported in the Policy Cycle contexts (BOWE; BALL; GOLD, 1992) - context of influence, text production and practical context, and the context of practice is the focus of the research. Data was collected through semi-structured interviews with managers of the analyzed HEIs, and questionnaires were applied to their teachers and students. The policy cycle method was used to analyze the Sinaes as a regulatory policy, quality inducer in higher education. The cycle was chosen for allow the articulation of political processes at macro and micro levels. The policy analysis contexts are interconnected, out of time, not linear. The analysis of Sinaes was permeated with some methodological aspects by critical discourse analysis (CDA). In the research it was found that the Sinaes establishes quality criteria, and by the evaluative acts linked concepts to the HEIs. The results revealed the limited knowledge of the managers on the construction context of Sinaes policy. The lack of knowledge by the influence context don???t unfeasible the discussion by Sinaes policy. Teachers and students recognize the text of the policy, but they don???t validate like quality reflex. The managers need to share information and results of the evaluation process, even also they not countersign in its entirety. In practice, they have consciousness of the excessive importance given to the National Examination of Student???s Performance (Enade), although not suitable for measuring quality. However, the indicators are used as instrument to attract students and generate rankings. For managers, the Sinaes is guiding improvements, but requires reinforcing its articulator character, valuing the self-assessment and regional characteristics.